Effectiveness of cross double mcdonald cerclage for intractable bleeding from a cervical varix in pregnant women - Yuya Fujibe; Tasuku Mariya; Masahito Mizuuchi; Shinichi Ishioka; Tsuyoshi Saito (Wolters Kluwer Medknow Publications, 2021)
Cervical varix during pregnancy is a rare condition, and standard management for bleeding from a varix has not been established. We performed cross double cervical cerclage and effectively stopped bleeding. A 41-year-old female had a twin pregnancy. The development of a cervical varix was observed during pregnancy and bleeding from ruptured varix started at 20 weeks of gestation. We performed surgical hemostasis by cervical cerclage. In the first cerclage, we could not stop the bleeding from the varix. For further restriction of blood supply to the cervical varix, we performed a second cerclage in a crossed position on a deeper side of the vagina than the first cerclage. Then the bleeding completely stopped and there was no bleeding until delivery. The "cross double McDonald cerclage" performed in our patient may be a useful modified cerclage method for stopping intractable bleeding from the cervix during pregnancy.